The Ocean Gene Atlas v2.0: online exploration of the biogeography and phylogeny of plankton genes. Issue Volume 50:Issue W1(2022) (10th June 2022) - Vernette, Caroline; Lecubin, Julien; Sánchez, Pablo; ,; Sunagawa, Shinichi; Delmont, Tom O; Acinas, Silvia G; Pelletier, Eric; Hingamp, Pascal; Lescot, Magali
Abstract: Testing hypothesis about the biogeography of genes using large data resources such as Tara Oceans marine metagenomes and metatranscriptomes requires significant hardware resources and programming skills. The new release of the 'Ocean Gene Atlas' (OGA2) is a freely available intuitive online service to mine large and complex marine environmental genomic databases. OGA2 datasets available have been extended and now include, from the Tara Oceans portfolio: (i) eukaryotic Metagenome-Assembled-Genomes (MAGs) and Single-cell Assembled Genomes (SAGs) (10.2E+6 coding genes), (ii) version 2 of Ocean Microbial Reference Gene Catalogue (46.8E+6 non-redundant genes), (iii) 924 MetaGenomic Transcriptomes (7E+6 unigenes), (iv) 530 MAGs from an Arctic MAG catalogue (1E+6 genes) and (v) 1888 Bacterial and Archaeal Genomes (4.5E+6 genes), and an additional dataset from the Malaspina 2010 global circumnavigation: (vi) 317 Malaspina Deep Metagenome Assembled Genomes (0.9E+6 genes). Novel analyses enabled by OGA2 include phylogenetic tree inference to visualize user queries within their context of sequence homologues from both the marine environmental dataset and the RefSeq database. An Application Programming Interface (API) now allows users to query OGA2 using command-line tools, hence providing local workflow integration. Finally, gene abundance can be interactively filtered directly on map displays using any of the available environmental variables. Ocean Gene Atlas v2.0 is freely-available at: https://tara-oceans.mio.osupytheas.fr/ocean-gene-atlas/ . Graphical Abstract: